First-trimester Doppler Ultrasound for Predicting Successful Management of Pregnancy with Recurrent Pregnancy Losses Due to Antiphospholipid Syndrome and Thrombophilia: A Cohort Study - Muhammad Adrianes Bachnas; Uki Retno Budihastuti; Eriana Melinawati; Nutria Widya Purna Anggraini; Robert Ridwan; Lini Astetri; Agung Sari Wijayanti; Atthahira Amalia Hafiizha; Muhammad Denny Gagah Pradana; Aliffudin Nur; Muhammad Alamsyah Azis; Wiryawan Permadi; et al. (Journal of Human Reproductive Sciences)
Background: Recurrent pregnancy loss (RPL) often stems from a hypercoagulable state that exacerbates conditions such as antiphospholipid syndrome (APS) and thrombophilia, leading to early placental issues. Although treatments such as low-molecular-weight heparin (LMWH) and low-dose aspirin (LDA) are used, outcomes vary. This study proposes using first-trimester Doppler ultrasound – specifically, uterine radial artery resistance index (URa-RI) at 8 weeks and uterine artery pulsatility index (Ut-PI) with pre-diastolic notching (Ut-notch) at 11–13 weeks — to better predict successful pregnancies and reduce risks of adverse outcomes. Aim: The aim of this study was to evaluate URa-RI, Ut-PI and Ut-notch between successful pregnancy and not successful and between pregnancy with adverse events and without. Settings and Design: The study was conducted in a clinical setting, using a retrospective cohort design on a sample of 72 patients with a history of two or more RPL episodes. Materials and Methods: Data on URa-RI measured at 8 weeks and Ut-PI and Ut-notch measured at 11–13 weeks were collected. Maternal characteristics – including age, BMI, number of pregnancy losses, etiopathology and immuno-inflammatory response – were considered in the analysis. Statistical Analysis Used: Comparative statistical analysis was performed on URa-RI, Ut-PI and Ut-notch data, evaluating their associations with pregnancy success and adverse outcomes. Variables were statistically compared between successful and unsuccessful pregnancies and also analysed for adverse events. Analysis was performed using SPSS (IBM, 27th edition). Chi-square tests were applied to nominal categories and multivariate logistic regression adjusted for age, body mass index (BMI), previous pregnancy losses, etiopathology and antinuclear antibody positivity. Primary outcomes (URa-RI, Ut-PI and Ut-notch) were reported with odds ratios and 95% confidence intervals (CIs). Results: Low URa-RI (<0.45) at 8 weeks gives a 16.4 times higher chance for the management to be successful and result in a healthy take-home baby (95% CI = 4.4–61, P < 0.0001). The mean URa-RI was also significantly higher in unsuccessful pregnancy (0.50 ± 0.09 vs. 0.38 ± 0.04, P < 0.0001). High Ut-PI and positive Ut-notch result in a significant increase of adverse event risk, which are 19.4 times and 8.1 times, respectively (95% CI = 4.2–51.6 and 3.12–20.5, P < 0.0001). Conclusion: This study demonstrates the utility of first-trimester Doppler ultrasound (URa-RI, Ut-PI and Ut-notch) in predicting pregnancy success and adverse events in patients with RPL, particularly those managed with LMWH and LDA. These ultrasound markers may provide valuable guidance in managing and anticipating outcomes in RPL cases related to thrombophilia and APS.